Spectrophotometric Methods for Determination of Tapentadol Hydrochloride - Mokhtar M. Mobrouk, Hamed M. El-Fatatry, Sherin F. Hammad, Aya A. Mohamed (Journal of Applied Pharmaceutical Science, 2013)
Two simple, fast, environmental friendly and reliable spectrophotometric methods were developed for determination of tapentadol hydrochloride in bulk and synthetic mixture containing the possible excipients. The first method is based on measuring the first derivative values of aqueous solution of the drug at 228 nm (method I) and the second method based on measuring the second derivative values at 235 nm (method II). Calibration graphs constructed at their wavelengths of determination were linear in the concentration range of tapentadol 5-60 μg.ml-1 for both methods. The proposed methods have been extensively validated as per ICH guidelines. The developed spectrophotometric methods in this study are simple, accurate, precise, specific and reproducible and can be directly applied to pharmaceutical dosage form.
Keywords: Tapentadol, Derivative spectrophotometry, First deri